Anthropometry measurements to determine nutritional status among cerebral palsy children: a scoping review - Mokhy, Mahnon Suria; Jamaluddin, Rosita; Ismail, Abd Rasyid; Siah, Woan Yie; Sulaiman, Norhasmah; Adznam, Siti Nur ‘Asyura; Ismail, Intan Hakimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
This article aimed to review the available anthropometry measurements used in the assessment of nutritional status among Cerebral Palsy (CP) children. Searched journals were from Medline, PubMed and Ovid published from 2015 to 2018. The search identified 443 articles, and eight studies met the criteria. Anthropometric measurements included weight, height, recumbent length, knee height, tibia length, Dual-energy X-ray absorptiometry (DXA), Bioelectrical impedance (BIA), Mid arm circumference (MUAC) subscapular skinfold (SFT), Triceps skinfold (TSF) and prediction equations. Body fat composition can be obtained by DXA, BIA, skinfold measurement, and also prediction equation. The predictive equation is the most reported method to determine nutritional status among CP. This review found that TSF and SFT are more accurate to determine body fat percentage when using together with the predictive equation. Besides, predictive equations using segmental length are reliable in estimating the height and can be used to evaluate the nutritional status using the specific CP growth chart.